UTILIZATION AND PRACTICE OF TRADITIONAL/COMPLEMENTARY/ALTERNATIVE MEDICINE (TM/CAM) IN SOUTH AFRICA - Peltzer, Karl (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The aim of this study was to conduct a systematic review of published and unpublished research investigating the prevalence of traditional, complementary and alternative medicine (TMCAM) use in the general population. Results found that use of a traditional and/or faith healer seemed to have decreased over the past 13 years (from a range of 3.6- 12.7% to 0.1%). The prevalence of traditional male circumcision was found to be 24.8% generally and 31.9% among the African Black racial group. The range of use of alternative and complementary medicine was from 0% to 2.2%. Local utilization surveys of TMCAM for the last illness episode or in the past year showed a variation in use of 6.1% to 38.5%. The prevalence of conditions treated at different TMCAM out-patients settings ranged from chronic conditions, complex of supernatural or psychosocial problems, mental illness, chronic conditions, acute conditions, generalized pain, HIV and other sexually transmitted infections. TM and probably CAM is used by substantial proportions of the general population, but differences in study design and methodological limitations make it difficult to compare prevalence estimates.